2008
DOI: 10.1177/112067210801800130
|View full text |Cite
|
Sign up to set email alerts
|

Suprasellar Germinoma and Late Perioptic Seeding

Abstract: Perioptic subarachnoid seeding may occur over a decade after presumed successful treatment of germinomas, suggesting the importance of lifelong observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The patient suffered rightsided facial numbness and pain. Moreover, Pereira et al 1 reported metastatic seeding along bilateral optic nerves in a patient 12 years after treatment of a suprasellar germinoma. There were concurrent lesions along the left trigeminal and facial (CN VII) nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient suffered rightsided facial numbness and pain. Moreover, Pereira et al 1 reported metastatic seeding along bilateral optic nerves in a patient 12 years after treatment of a suprasellar germinoma. There were concurrent lesions along the left trigeminal and facial (CN VII) nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit very rarely, leptomeningeal seeding along the optic nerve (CN II) has been reported in patients with intracranial germinoma 1 . But even then, direct leptomeningeal seeding of an IG -or of any primary CNS tumor -along the intracranial course of the trigeminal nerve, as found in our patient, has seldom been observed.…”
Section: Discussionmentioning
confidence: 99%
“…29 This seeding may occur in a delayed manner and has been observed to occur as long as 12 years after initial diagnosis. 30
Figure 2 Midline sagittal T1 MRI with gadolinium of bifocal pineal region/suprasellar germinoma in a 15-year-old female patient. The patients had signs and symptoms of headache, bitemporal hemianopia, and polydipsia.
…”
Section: Diagnosismentioning
confidence: 99%
“… 54 Because long-term outcomes remain unclear, continual follow-up is recommended even after complete remission has been achieved, 54 perhaps even for life. 30 …”
Section: Managementmentioning
confidence: 99%
“…Extra‐axial sites have been reported, mostly in Asian populations, in the thalamic and basal ganglia, corpus callosum, and ventricles . Initial localization in or secondary seeding dissemination to the optic nerves has seldom been reported.…”
Section: Introductionmentioning
confidence: 99%